Pengaruh Cybersecurity Terhadap Layanan Mobile Banking Bank Syariah Di Kota Pekanbaru - Abdul Gani, Indah Nursifa; Syahrullah, M.; Munthe, Marabona (Journal of Islamic Banking, Economics and Finance, 2025)
The development of digital technology has encouraged the banking sector, including Islamic banking in Indonesia, to introduce mobile banking-based services in an effort to improve service quality and meet customer needs quickly, easily, and efficiently. However, the growth of this digital service is also accompanied by an increase in the potential for cyber threats that can compromise data security, customer trust, and convenience in transactions. This study aims to analyze the impact of cybersecurity on Islamic mobile banking services in Indonesia, specifically on aspects of security, system reliability, and customer satisfaction. The research method used a quantitative approach by distributing questionnaires to customers using Islamic mobile banking services. Data were analyzed through validity and reliability tests and linear regression analysis to determine the relationship between cybersecurity variables and the quality of digital banking services. The results show that good cybersecurity implementation has a significant influence on customer trust and satisfaction, as well as improving perceptions of the quality of Islamic mobile banking services. These findings confirm that digital security aspects are a critical factor that Islamic banks need to consider in developing mobile banking services, to support sustainability, competitiveness, and public trust in the Islamic banking system in the digital era.